Perspektif Baru Pendidikan Kewarganegaraan dalam Dimensi Sejarah: Belajar dari Kebangkitan Jepang: - - Nugroho, Dedy Ari; Andyastuti, Etty; Wiranata, Irawan Hadi; Rusmaniah, Rusmaniah; Indriyani, Putri Dyah (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
This research article contains a review of the results of a literature review that focuses on efforts to rebuild civic education from post-conflict conditions in Japan. The implementation of civics learning in Japan is an interesting study to explore and take good things to build the quality of civic education in Indonesia. Citizenship education needs to be explored and continuously developed to be relevant to the demands and developments of the times. Building the mental aspect and building the nation's love for its country needs to be done by implementing quality Citizenship Education learning. This research article was compiled using a phenomenological qualitative data approach. This article contains data on the findings of the study in a series of words that can describe data based on facts. The type of qualitative data used in this article is a phenomenological descriptive data type. The results obtained from the results of the study carried out are manifested in the following discussion. (1) The history of the development of Citizenship Education in Japan, (2) The learning approach of Citizenship Education in Japan, (3) Analysis of the learning of Citizenship Education in Japan. The results revealed in this article contribute to the design of learning in civic education in Indonesia. The articles made will also contribute to the all-round insight of improving the nation's mentality in facing various global challenges.